Acid violence: a burning issue in Bangladesh - Akhter, Gulshan Ara; Islam, Farzana (Ibrahim Medical College Journal, 2014)
Acid violence is a barbaric form of violence in Bangladesh. Acid violence also called acid throwing or vitriolage, is defined as the act of throwing of strong corrosives on face and body of a person with the intention of causing permanent disfiguration, intense pain, scarring and sometimes blindness. All of these injuries are considered as grievous hurt under section 320 of B.P.C (Bangladesh Penal Code). For the last few years it is on the rise in both urban and rural areas of Bangladesh. The perpetrators are mostly men and adolescent boys. The overwhelming majority of the victims are women and many of them are girls and young females. Recently, however, there have been acid attacks on children, older women and also men. These attacks are often the result of family and land dispute, dowry demands or a desire for revenge due to failure in love affairs or marriage proposals. It is considered as one of the extreme forms of repression and violation of womens right. This review article is aimed to focus on the present situation of this barbaric act of vengeance against women and young adolescent girls with regard to frequency, causes, long term consequences and creating public awareness on the issue by tightly regulating the sale and transport of acid as well as enacting harsher penalties for perpetrators. Data collection is based on information from Dhaka Medical College hospital, One Stop Crisis Center (OCC), Acid Survivors Foundation, Naripokkho Action Aid and several Dhaka based organizations. DOI: http://dx.doi.org/10.3329/imcj.v7i1.17744 Ibrahim Med. Coll. J. 2013; 7(1): 18-20